Effects of selected Malaysian herbs on healthy ageing / Annie George V. K. George - Annie George , V. K. George (2018)
Oxidative damage caused by free radicals plays an important role in accelerating ageing and age-related diseases including neurodegenerative diseases, inflammation (rheumatoid arthritis), cardiovascular disorder, immunosenescence and cancer. The life expectancy of the world is rising with an estimated 29% of the world population reaching age 60 by 2025. This would lead to an increase in the number of people acquiring age-related chronic diseases which would reduce the quality of life and further burden society and government. The free radicals can be quenched by endogenous antioxidant enzymes or exogenous antioxidants. Herbal antioxidants have potentially multifunctional targets in quenching free radicals and protecting health. Malaysia is home to many medicinal plants and herbs which have been used traditionally for the treatment of diseases. They however lack scientific evidence proving the acclaimed benefits. In this research, herbs with a long history of traditional use were investigated for their potential as agents for preventive healthcare potentially via their antioxidative properties. Kesum (Polygonum minus) was established as very high in antioxidant properties with acetylcholinesterase inhibitory activities - the enzyme target for neurological drug therapies. The Kesum extract was also confirmed to possess compounds which can permeate cells thus protecting the cell from oxidative damage from within. The extract was able to attenuate scopolamine-induced memory deficit in vivo at a dosage of 100 mg/kg body weight. Kesum also has anti-inflammatory properties inhibiting lipoxygenase and cyclooxygenase enzyme. The reduction of paw oedema in vivo in just 4 hours, in addition, potentially places the plant as a remedy for arthritis. The Misai Kuching (Orthosiphon stamineus) which is known to be highly antioxidative was found to possess adenosine 2 receptors antagonist activity which is also a target for drug therapy against neurological diseases. This was further qualified in vivo whereby a dose of at least 300 mg/kg body weight of extract improved learning and memory. The anti-ageing and antioxidant property of Tongkat Ali (Eurycoma longifolia) has also been elucidated. Additionally, the immunomodulatory effects were evaluated as immunosenescence is a major contribution to morbidity and mortality among the aged. The Tongkat Ali was able to improve the immune state by increasing the number of naive T-cells, lymphocyte and reducing the immunological age which is a patented scoring system which measures T cell proliferation activity and number, which is normally higher in younger persons. Tongkat Ali in combination with Kesum, improved the mens’ quality of life, sexual and physical wellbeing. It was also able to improve testosterone levels which reduce with age and environmental stress. Therefore, the supplementation of antioxidant herbs with its multifunctional pharmacological targets are able to sequester free radicals that cause oxidative stress, thus proving to be agents for preventive healthcare and alternative therapy in healthy ageing as evidenced in this research programme.